Dyplomacja brytyjska wobec zabiegów Rosji o wyłączne wpływy w Mandżurii (październik 1901 r. – sierpień 1903 r.) - Damski, Przemysław Piotr (Acta Universitatis Lodziensis. Folia Historica, 2012)
After the collapse of the ‘Boxer Rebellion’, Russia wanted to take an advantage of the fact that hers troops occupied Manchuria and to obtain the exclusive influence in this country. This was contrary to the Open Door policy which had been declared by the United States, Japan, Great Britain and other European Powers, including the Russian Empire, since 1899. These had made London to rethink his own policy in the Far East. British hadn’t much interests in Manchuria. However, in their point of view rise of Russian power in China would destabilize situation in the Celestial Empire and encourage other Powers to ‘curving a Chinese pie’. It would affect British interests in Qing’s State which were larger than any other Power. Russian railway businesses and her ambition in North-East China were also a danger to similar British investments. This was one of the reasons to abandon a policy of so called ‘splendid isolation’. First visible effect of this decision was the Anglo-Japanese Alliance of January 30th, 1902. The treaty was a defensive one but clearly anti-Russian. Simultaneously Secretary of State for Foreign Affairs, the Marquess of Lansdowne, raised that Russian policy was contrary to the Open Door policy. In fact Britain was concerned on defending her own interests instead of Open Door which was only a slogan for her. During February and March of 1902 London wasn’t able to develop a common policy with his ally – Japan, and also with the United States which appeal for the ‘open door’ once again (February 1st, 1902). St Petersburg took the opportunity and published with Paris the Franco-Russian Declaration of March 16th, 1902. Foreign Office was ready to deal with Russian Government, but the tenacity of the latter convinced Whitehall that Britain should act in accord with Tokyo and Washington. This made Russia to sign an agreement with China on April 8th, 1902. Between April 8th, 1902 and April 8th, 1903 British were waiting and observing the results of Russian evacuation from Manchuria. At this time they weren’t especially concerned about the situation in North-East China as far as Russians were accomplishing the terms of the agreement. They only singed a commercial treaty with the Celestial Empire of September 5th, 1902. This was changed by St Petersburg announcement about new terms of evacuation of Russian soldiers (April 8th, 1903). This time London, as well as Washington, didn’t force Russia to fulfil her treaty obligations. Only Tokyo whose interests were most endangered strongly opposed Russia’s plans. Lansdowne who was planning an agreement with France was also thinking about rapprochement with Russia. Lack of strong reaction from Washington on St Petersburg’s demands convinced Whitehall of rightness of his own policy. British abandoned the phrase of Open Door and de facto recognized Russian influences in Manchuria in the Lansdowne’s proposition of July 29th, of 1903. Russia answered with formation of the Far Eastern Viceroyalty. This had ended the first attempt of British-Russian rapprochement but didn’t stop Franco-British talks which leaded to so called Entente Cordiale of April 8th, 1904. It proves that Britain hadn’t been committed to the Open Door policy which was only an instrument securing her interests in Qing’s Empire. The alliance with Japan had the same task. When British politicians had realized that both instruments hadn’t brought expected results they started to search a better way to secure British interests. The only reasonable step for Whitehall, who wanted to avoid a war, was an agreement with Russia.